The Effect of DER, Firm Size, and CR on PBV with ROE as an Intervening Variable - Pustika, Titin Hestri; Hariyanto, Dedi; Safitri, Heni (Jurnal Manajemen Bisnis, 2022)
Research aim: The study is intended to analyze the influence of debt-to-equity ratios, firm size, and current ratio on price-to-book value using the return on equity as an intervening variable.Design/Methodology/Approach: The population in this research was basic materials sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. Meanwhile, the number of samples in this study was 70, collected by purposive sampling. Research findings: This study confirmed that DER had a good and strong effect on ROE. Firm size and CR had no considerable influence on ROE. ROE had a significant positive effect on PBV, while DER, firm size, and CR had no significant impact on PBV. In addition, ROE was susceptible to being an intervening variable of a DER but was not susceptible to being an intervention variable of firm size and CR variables.Theoretical contribution/Originality: The return on equity (ROE) variable served as the intervening variable in the study, while in previous studies, DER, firm size, and CR variables were not intervened by ROE.Practitioner/Policy implication: Researchers suggest that investors can use other variables to make investment decisions. Researchers can also further develop broader objects, such as using other sectors and adding or replacing other variables to determine the feasibility of investing.Research limitation: The scope of this study was relative, and there were many insignificances due to the limited variables and sectors used. Hence, increasing the number of variables and a wider sector will be able to strengthen this research’s outcomes. Further research must be able to produce significant values and affect the variables in question.